Effect of processing temperature on utilization of whole soybeans by young calves - I.E.O. Abdelgadir; J.L. Morrill; J.A. Stutts; B. Morrill (Kansas Agricultural Experiment Station Research Reports, 1984)
Two trials were conducted to determine the optimum conditions for processing whole soybeans for young calves. In the first trial, laboratory procedures and a nitrogen balance study were used. This information was used to design the second trial in which raw and processed soybeans were evaluated in an 8-wk growth trial using 96 Holstein day-old calves. Starters contained soybean meal (SBM), SBM with added fat, raw soybeans, or soybeans processed at 280, 340, or 375°F in a California Pellet Mill Jet-Sploder. Calves fed the starters containing soybeans processed at 340 consumed more feed, gained faster, had lower fecal scores (less scours), and less mortality.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Temperature; Soybeans; Growth rate; Feed consumption